Suspended Marine Litter in New Calabar/Bonny Estuary System and Amadi Creek, Rivers State, Nigeria - Uche, Arinze O.; Bolaji B., Babatunde (International Journal For Research In Applied And Natural Science, 2020)
A study of Nine coastal communities along the New Calabar/Bonny Estuary and Amadi Creek in Rivers State was conducted to: Identify and Geo-reference affected navigable channels in Rivers State; create a map of affected navigable channels in the state; qualitatively and quantitatively characterize floating marine debris in affected channels; Delineate the affected channels; and create awareness among coastal communities on suspended litter hazards. The data for average depth revealed that the water body in Diobu had the highest depth of10 m while Nkpogu and Ogunabali had the least depth of 4 m; average width was highest (100m) at Ukwa Aki while the least (25m) was recorded in Elekahia. The average flow velocity was highest (1.4 m/s) at Amatangbolo, and lowest (0.5 m/s) at Amadi-Ama. Characterization of suspended debris showed that the debris comprised of plastic, nylon, can, and foil. Plastic and nylon recorded the highest amount, accounting for over 70%. Average weight of suspended material per square kilometer ranged from the least value of 7553.33 kg/km2 at Amatangbolo to the highest value of 126,410 kg/km2 at Ogbunabali. Based on 20 tons capacity dumper trucks estimate, this study location would require between 1-7 dumper trucks to evacuate the suspended debris per square kilometers. In conclusion, plastics and nylon are the top ranking floating litter in the study area and as they do not biodegrade easily is a serious concern to the whole ecosystem wellbeing. Therefore it is our duty to safeguard our environment through global best practices and enlightenment campaigns.